2018
DOI: 10.1246/bcsj.20180214
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous CeO2 Supports Prepared from Amorphous Alloys: Enhanced Catalytic Performance for Hydrogen Generation from Formic Acid

Abstract: Nanoporous CeO2 samples as supports were prepared by chemical dealloying Ce-Al amorphous alloy, followed by synthesis of Au-Pd/CeO2 catalysts. The synthesized Au-Pd/CeO2 catalysts showed higher catalytic activity for hydrogen generation from formic acid than catalysts using supports prepared from a crystalline alloy precursor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…the specific atomic range of 710 at%Ce. 24) CeAl alloy (Ce:Al = 8:92) ingots were prepared by arc-melt technique from pure Ce and Al lumps in a highly purified Ar atmosphere. Ce 8 Al 92 amorphous alloys in the form of ribbons were prepared from CeAl ingots through liquid quenching by a single roller melt-spinning method.…”
Section: +1mentioning
confidence: 99%
See 1 more Smart Citation
“…the specific atomic range of 710 at%Ce. 24) CeAl alloy (Ce:Al = 8:92) ingots were prepared by arc-melt technique from pure Ce and Al lumps in a highly purified Ar atmosphere. Ce 8 Al 92 amorphous alloys in the form of ribbons were prepared from CeAl ingots through liquid quenching by a single roller melt-spinning method.…”
Section: +1mentioning
confidence: 99%
“…1923) In this study, the CeAl amorphous alloy was used as a precursor to prepare CeO 2 support. Al could form amorphous alloys with Ce in the specific composition range 24) and easily extracted using NaOH solution. Nanoporous CeO 2 from CeAl crystalline alloy was also prepared to clarify the effect of atomic arrangement of precursors on the structure and catalyst support properties of nanoporous CeO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…9) In our previous studies, 1013) the CeO 2 porous particles prepared from dealloying of a CeAl amorphous alloy as the precursor alloy were found to be higher in surface area than a commercial CeO 2 , controlling their size and morphology as a function of dealloying time and precursor crystallinity. It was clearly showed that the catalysts composed of AuPd, 10) Ru, 11) Ni, 12) and Au 13) supported-CeO 2 from an amorphous alloy showed higher catalytic activity in hydrogen generation 1012) and oxidation 13) reactions than use of CeO 2 prepared from a crystalline alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Amorphous alloys have a disordered atomic arrangement unlike their crystalline counterparts, and they have been attracting the attention of researchers in various fields due to their unique properties derived from the atomic arrangement. 13) In recent years, it has been reported that amorphous alloys exhibit excellent catalytic performances in comparison with those of the corresponding crystalline alloys. 47) CeO 2 is widely used as a catalyst support in, for instance, three-way catalysis, CO oxidation, and the water gas shift reaction, due to its excellent durability and oxygen-storage capacity.…”
Section: Introductionmentioning
confidence: 99%